Postmodern metadrama in Martin McDonagh's A Very Very Very Dark Matter - Kolahjooei, Farzad (Orbis litterarum, 2025)
This paper explores Martin McDonagh's A Very Very Very Dark Matter as a postmodern metadrama. I will take parody as an umbrella term under which various other concepts, including intertextuality, discontinuity, and irony, create a self‐reflexive network to reconsider some of the grand narratives in the West, patricularly the discourses of writing and history. The alternative world that McDonagh imagines in his play through combining fact and fiction, I will argue, fits well in such a networked consideration of metadrama as it displays a radical perspective that asks essential questions about originality, the Western literary canon, and political history.